PEMBERIAN PEKERJAAN PELAYANAN PARKIR DITEPI JALAN KEPADA PIHAK KE III (TENAGA KERJA OUTSOURCING) DAN MASALAH HUKUMNYA - Agus Salim A (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Parking is one of the complement in a shopping building that results can support local government revenues. Based on the results of preliminary studies, the implementation of the agreement were not implemented many of the provisions of the applicable contents of the agreement. The purpose of this study was to determine the policy implementation service levies parked at the curb public conducted by the Department of Transportation Parking Management UPTD Samarinda with based on indicators of policy implementation. constraints faced their mastery parking locations by persons who are not responsible, incidental parking offenders who do not report their activities, parking attendants who are not obedient, very rapid growth of vehicle, the number of labor inspectors is inadequate parking. Based parking management policy implementation submission of the Department of Transportation has now handed over to third parties (Outsourcing) conducted in the area of parking in the city of Samarinda. Based on this, researchers interested in conducting research in the form of a thesis with problems: a) How is the implementation of cooperation agreements parking management between the regional government with parking management to a third party labor (outsourcing)? B) What factors are some that hinder the implementation of the policy of surrender parking management to a third party labor (outsourcing)? Jenispenelitian is juridical empirical data used are primary data and secondary data used through library research and field study. Data were processed through the identification process, editing, data classification, data preparation and conclusion then analyzed descriptively qualitative. Keywords: policy, parking management, and the Department of Transportation